2013
DOI: 10.1200/jco.2012.46.8470
|View full text |Cite
|
Sign up to set email alerts
|

Future of Clinical Genomics in Pediatric Oncology

Abstract: The somatic genomic alterations in pediatric cancers to some extent overlap with those seen in adult cancers, but the exact distribution throughout the genome and the types and frequency of alterations differ. The ultimate goal of genomic research in children, as with adults, is translation to the clinic to achieve more accurate diagnosis, more precise risk stratification, and more effective, less toxic therapy. The genomic features of pediatric malignancies and pediatric-specific issues in clinical investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 119 publications
0
27
1
3
Order By: Relevance
“…While hematologic malignancies comprise nearly 40% of childhood cancer [14], our results did not show a predilection for hematologic malignancies. Although not statistically significant, a slight predominance of solid tumors over hematologic malignancies was observed.…”
Section: Discussioncontrasting
confidence: 50%
“…While hematologic malignancies comprise nearly 40% of childhood cancer [14], our results did not show a predilection for hematologic malignancies. Although not statistically significant, a slight predominance of solid tumors over hematologic malignancies was observed.…”
Section: Discussioncontrasting
confidence: 50%
“…In addition, targeted agents are being increasingly used in pediatric cancers, and the need for individualized comprehensive genomic evaluation to identify potential molecular targets has become increasingly important 1215 . An estimated 5% of pediatric solid tumors may harbor actionable genetic mutations, with 10% of mutations found in the germ-line 1618 . Additionally, pharmacogenomic and pharmacodynamic studies utilize biomarkers from tumor tissue to evaluate modulation of the intended molecular targets 19 .…”
Section: Introductionmentioning
confidence: 99%
“…He also referred to the role of molecular biology and its impact in diagnosis, prognosis, and the treatment of PBT, and to the necessity of identifying biologic pathways and to develop a risk stratification based on clinical and biologic prognostic factors [51, 52]. …”
Section: Session 2: Clinic Experience In Paediatric Cancermentioning
confidence: 99%
“…Apart from confirming that the drug combination was antiangiogenic, some relevant findings indicated that increased levels of CEC could be useful for detecting progression and, more importantly, the baseline levels of VEGF or the VEGF/sVEGFR-2 ratio could be useful as early predictors of response because they were significantly correlated with TTP [51]. …”
Section: Session 3: Clinical Experience In Adult Cancermentioning
confidence: 99%